Augustine's Timaeus 41ab - Yudin, Victor; Counet, Jean-Michel; Université Catholique de Louvain-la-Neuve. Institut Supérieur de Philosophie (Louvain-la-Neuve Université Catholique de Louvain-la-Neuve, 2012)
Contrary to P. Alfaric and the partisans of Augustine&#x2019%x;s conversion to any form of Plato(nism), this thesis is a textual proof that Augustine&#x2019%x;s Plato is a smart rhetorician who advocates Christian ideas. Tim 41 a7&#x2010%x;b6 is the text par excellence Augustine borrows from Plato. Sixteen times of Augustine&#x2019%x;s application in the course of his writing is a projection upon the original of a Resurrection doctrine which is simply not there. His exegesis is exclusively based on Cicero&#x2019%x;s stocizing translation, and is seemingly directed at Porphyry who attacks the bodily resurrection also with sixteen arguments. Augustine is keen to teach but is not familiar with other numerous interpretations of this passage. None of the previous Neo&#x2010%x;Platonists or Apologists who scrutinized Tim 41a7&#x2010%x;b6 has ever attempted a similar reading. With such a creative yet biased treatment of sources Augustine could never convince any expert. His secret agenda is to convert a common literate man by means of a rhetorical reference to the pagan authorities.
Diss. doct
Keywords: Augustine; Plato; Stoicism; De civitate Dei; Resurrection; Divine omnipotence; Calcidius; Timaeus; Platonists; Neoplatonists; Porphyry; Against the Christians; Proclus; Apologists; Cicero; 276 -- Latijnse patrologie-:-Filosofie. Psychologie--AUGUSTINUS